2006
DOI: 10.4049/jimmunol.177.11.7820
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory CD4+ T Cell Subset in the BB Rat Model of Autoimmune Diabetes Expresses Neither CD25 Nor Foxp3

Abstract: Biobreeding (BB) rats model type 1 autoimmune diabetes (T1D). BB diabetes-prone (BBDP) rats develop T1D spontaneously. BB diabetes-resistant (BBDR) rats develop T1D after immunological perturbations that include regulatory T cell (Treg) depletion plus administration of low doses of a TLR ligand, polyinosinic-polycytidylic acid. Using both models, we analyzed CD4+CD25+ and CD4+CD45RC− candidate rat Treg populations. In BBDR and control Wistar Furth rats, CD25+ T cells comprised 5–8% of CD4+ T cells. In vitro, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 58 publications
4
17
0
2
Order By: Relevance
“…17,62 In addition, other even less well-defined Foxp3-negative regulatory cell populations have recently been described. 63,64 Preliminary data from our laboratory actually suggests that multiple regulatory populations may be induced by ATG (M.C.R., J.D., J.M.W., S.R.N., and S.S., unpublished data, January 2006). Nevertheless, given the significant suppressive effects of the mixed population of splenocytes following mATG treatment, the identification and purification of the suppressive populations should yield greater suppressive potency and provide additional understanding of mATG effects.…”
Section: Discussionmentioning
confidence: 96%
“…17,62 In addition, other even less well-defined Foxp3-negative regulatory cell populations have recently been described. 63,64 Preliminary data from our laboratory actually suggests that multiple regulatory populations may be induced by ATG (M.C.R., J.D., J.M.W., S.R.N., and S.S., unpublished data, January 2006). Nevertheless, given the significant suppressive effects of the mixed population of splenocytes following mATG treatment, the identification and purification of the suppressive populations should yield greater suppressive potency and provide additional understanding of mATG effects.…”
Section: Discussionmentioning
confidence: 96%
“…For the genotyping of the samples, we acknowledge the University of Eastern Finland and the Mutation Analysis Core Facility at Karolinska Institutet. Thomas Dahllund, 11 Johanna Granvik, 12 Maarit Haapalehto-Ikonen, 13 AnuMaaria Hämäläinen, 14 Hanna Huopio, 15 Christian Johansson, 16 Anne Kinnala, 17 Jussi Korhonen, 18 Paavo Korpela, 19 Maarit Korteniemi, 20 Pentti Lautala, 21 Kaija Lindströ m, 22 Päivi Miettinen, 1 Taina Mustila, 23 Anja Nuuja, 24 Päivi Nykänen, 25 Jussi Ojanperä, 26 Anne Putto-Laurila, 5 Marja-Terttu Saha, 4 Juhani Sankila, 27 Anne-Maarit Suomi, 6 Sirpa Tenhola, 28 Pentti Varimo, 29 Riitta Veijola, 8 Ritva Virransalo, 30 Pentti Vuolukka, 31 …”
Section: Acknowledgmentsunclassified
“…The spontaneously diabetic BioBreeding diabetes-prone rat has a recessive frameshift mutation in the Gimap5 that leads to a truncated form of the protein and a lymphopenic phenotype (15)(16)(17). One of the causative mechanisms could be the Th17/T regulatory cell (Treg) balance and the ability of Tregs to suppress Th17 function resulting from Gimap5 misfunction (18)(19)(20)(21)(22). Also, the Gimap5-deficient mouse T cells show poor proliferation and the mouse is phenotypically lymphopenic (23).…”
mentioning
confidence: 99%
“…T1D patients and the animal models for T1D (non-obese diabetic mouse and BBDP) display reduced levels or function of their regulatory T cells [16][17][18][19]. It was shown that restoration of the defect in regulatory T-cell function in BBDP rats by adoptive transfer with functional regulatory T cells from autoimmune diabetes-resistant BB rats, prevents autoimmune diabetes development [16][17][18]. Moreover, also in vivo expansion of Tregs in BBDP rats by super-agonistic αCD28 antibodies completely prevented autoimmune diabetes development [22].…”
Section: Discussionmentioning
confidence: 99%
“…T1D patients display decreased numbers or function of Tregs and therefore have a reduced capacity to suppress autoreactive T-cell reactions against beta-cell (auto)antigens [15]. Also, in the two most commonly used animal models for T1D (non-obese diabetic mice and BB rats), CD4 + CD25 + Tregs have been characterized and shown to be involved in the pathogenesis of autoimmune diabetes [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%